Pengaruh Live Streaming Dan Kualitas Produk Terhadap Keputusan Pembelian Produk Skintific Pada Aplikasi Tiktok Shop Di Kota Medan - Diniati, Diniati; Helmi, Tengku Ahmad; Yudha, Tri Kartika (Universitas Islam Islam Sumatera Utara, 2024)
This study aims to analyze the influence of live streaming and product quality on purchasing decisions for Skintific products at TikTokShop Medan. Using a quantitative approach, a survey was conducted on 200 respondents who had purchased Skintific products through TikTokShop. Data were collected through an online questionnaire covering the variables of live streaming, product quality, and purchasing decisions. Data analysis used the Partial Least Square (PLS) method to evaluate the relationship between variables and test the research model. The results showed that both live streaming and product quality had a positive and significant influence on purchasing decisions. Live streaming was found to have a stronger impact, indicating the importance of real-time interaction and product demonstration in influencing consumer decisions. Product quality was also shown to be an important factor, emphasizing that consumers still consider the intrinsic aspects of the product even in the context of online shopping